PELATIHAN PEMBELAJARAN PENDIDIKAN AKHLAK PADA SANTRI DI PONDOK PESANTREN AT-TAUBAH KARAWANG - Aenul Yakin (SABA JAYA PUBLISHER, 2023)
Moral education is the main capital in advancing a nation because the main capital in development is akhlakul karimah. Islamic boarding schools are Islamic educational institutions that are trusted by the community as forming the morals of effective students. Learning Training and Concepts Moral education in Islam is education that recognizes that in human life This research is a qualitative research. The subjects of this study were caregivers, ustadz and students at the AtTaubah Karawang Islamic Boarding School. Methods of data collection using observation techniques, interviews, and documentation. The results of this study state that: 1) Implementation of the concept of moral education for Imam Al Ghazali is categorized as well implemented, shown through the contributions of caregivers and ustadz making recitation schedules and scientific contributions; 2) Efforts made by caregivers and ustadz in implementing the concept of moral education, namely: a) Providing guidance; b) Giving Tausiyah; c) Providing exemplary; d) Apply Habits; 3) Supporting factors in implementing the concept of moral education, namely: a) Cooperation between caregivers and ustadz; b) Parental Support; c) Facilities. 4) The inhibiting factors in implementing the concept of moral education are: a) worldliness; b) Limited facilities and infrastructure.